PENANAMAN EMBRIO PADA RAHIM ISTRI YANG LAIN - Najib Junaidi; Ahmad Musta'in Syafi'ie (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2023)
This paper discusses the practice of IVF (in vitro fertilization) by another wife's womb. This practice was declared haram by the fatwa of the Indonesian Ulama Council on June 1979. The reason is it will cause complexity in matters of inheritance. Especially, between child and owner of the ovum and surrogate mother. This research is a qualitative research with normative juridical approach. This research is a library research. This research use documentation techniques. This study concluded that the complexity in the inheritance problem that is feared in the MUI's fatwa can be overcomed by determining their nasab relationship. Because the nasab relationship is one of the reasons for inheritance. So the authors conclude that the practice of IVF from husband and wife by another wife's womb is legally, and the children born through the process end up with surrogate mother who have conceived and given birth. Keywords: Fatwa, embryo transfer, surrogate mother, MUI. Daftar Pustaka Abdul Azis Dahlan, Ensiklopedi Hukum Islam, cet. 1 (Jakarta: Ichtiar Baru Van Hoeve, 1996) Abdul Haq, Formulasi Nalar Fiqih Telaah Kaidah Fiqih Konseptual, Buku kedua, (Surabaya Kaki lima, 2006) Abdur Rahman Ghazali, Fiqih Munakahat, (Jakarta: Prenada Media, 2003) Abdurrahman Al-Jaziri, al-Fiqh ala al-Madzahib al-arbaah, (Beirut, Libanon Dar al-kutub al-ilmiah, jilid IV, cet.IV) ––––––––, Kitab al-Fiqh (Mesir, Maktabah al-Tijāriyyah al-Kubrā, 1969 Abdurrahman Al-Jaziry, al -Fiqh 'ala Madzahtbi al-Arba'ah Juz IV, (Beirut Darul Haya'al-Turbal-Araby, 1969) Abduttawab Hakal, Rahasia Perkawinan Rasulullah Poligami dalam Islam vs Monogami Barat (Cet. I; Jakarta: Pedoman Ilmu Jaya, 1993) Abû al-Fidâ al-Hafizh ibn Katsîr al-Dimasqî, Al-Bidâyah wa al-Nihâyah, (Beirut: Dâr al-Kutub al-‘Ilmiyyah, t.t.) Abû Hâmid Muhammad ibn Muhammad ibn Muhammad al-Ghazâlî, Al-Mustashfâ, (Beirut: Dâr al-Fikr, 1998) Abû Ishâq al-Fayruzabadî al-Syayrâzî, Al-Lumâ’ fi Ushûl al-Fiqh Abû Zahrah, Târîkh Madzâhib al-Fiqhiyyah, (Kairo: Mathba’ah al-Madanî, t.t.) Ahmad Hasan, Analogical Reasoning in Islamic Jurisprudence, (Delhi: Adam Publisher, 1994) Ahmad Hasan, Pintu Ijtihad Sebelum Tertutup, terj oleh Agah Garnadi (Bandung: Pustaka, 1994) Al Amin, Habibi. "Guardians Concept in Qur'an Perspective." Shakhsiyah Burhaniyah: Jurnal Penelitian Hukum Islam 6.1 (2021): 95-114. Al Amin, Habibi. "Penciptaan Adam; Mendialogkan TafsiR Marah Labid dengan Teori Keadilan Gender." An-Nuha: Jurnal Kajian Islam, Pendidikan, Budaya Dan Sosial 1.1 (2014): 17-44. Al Amin, Habibi. "Tafsir Sufi Lataâ€™ if al-Isyarat." SUHUF 9.1 (2016): 59-77. Taufiqurrahman, Zaky Fajar, and Habibi Al Amin. "Desain Pembelajaran Literasi Kitab Kuning Melalui Metode Sorogan dalam Meningkatkan Pemahaman Agama Islam." Syntax Literate; Jurnal Ilmiah Indonesia 6.2 (2021): 1467-1474.